Hydrothermal Method to Synthesize Nanomagnetite by Water Extract of Averrhoa bilimbi : Effect of Time and Reactor Size - Arif, Zulhan; Ismawati, Iis; Hikmah, Anisa Nurul; Saprudin, Deden (Indonesian Scholar Society, 2023)
Nanomagnetite was synthesized using water extract of bilimbi (Averrhoa bilimbi). The high citric acid content has the potential as a reducing agent in the synthesis of magnetite using the hydrothermal method. The synthesis was conducted using different sizes of hydrothermal reactors, 50, 150, and 1700 mL. The results showed that a reactor with a volume of 150 mL and a synthesis time of 12 h was the best condition for synthesis. The results obtained from X-ray diffraction analysis showed that in the best conditions, the crystallinity level was 74.4%, the ratio of product to volume was 3.7×10–2 g/mL, the Fe content in magnetite was 22.0%, the Fe content in the remaining liquid was 0.02%, the Fe ratio was 96.9%, and the ammonium content in the solution was 1.24% w/v. The best conditions were 150 mL reactor and 12 hours synthesis.